New Aspects of Gene-Silencing for the Treatment of Cardiovascular Diseases - Hans-Peter Wendel; Bernd Neumann; Christian Schlensak; Almuth Zech; Nadja Perle; Olivia Koenig; Tobias Walker; Andrea Nolte (MDPI AG, 2013)
Coronary heart disease (CHD), mainly caused by atherosclerosis, represents the single leading cause of death in industrialized countries. Besides the classical interventional therapies new applications for treatment of vascular wall pathologies are appearing on the horizon. RNA interference (RNAi) represents a novel therapeutic strategy due to sequence-specific gene-silencing through the use of small interfering RNA (siRNA). The modulation of gene expression by short RNAs provides a powerful tool to theoretically silence any disease-related or disease-promoting gene of interest. In this review we outline the RNAi mechanisms, the currently used delivery systems and their possible applications to the cardiovascular system. Especially, the optimization of the targeting and transfection procedures could enhance the efficiency of siRNA delivery drastically and might open the way to clinical applicability. The new findings of the last years may show the techniques to new innovative therapies and could probably play an important role in treating CHD in the future.